Knowledge representation in russian and european tradition - Victoria V. Dobrova; Tatiana Koryakina Antunes (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2020)
Knowledge representation is a fundamental question in philosophy, pedagogy, linguistics, psychology and artificial intelligence. This paper examines the achievements in the field of creating knowledge-based systems that exist in Russian and European practice. We employed the methods of cross cultural content analysis and meta analysis to analyze various sources of information, to interpret definitions, and to increase the validity of the conclusions. The following problems are highlighted: the definition of knowledge and its types; the interplay between knowledge itself, its representation, and the physical world; approaches to knowledge representation; representation schemas for procedural and declarative knowledge types. The findings of the research illustrate that in Russian science, the problem of knowledge representation is associated with the problem of knowledge as such and its representation in our psyche, in contrast to European practice where the problem is considered to be purely applied. Theoretical contributions and practical implications discussed in the paper contribute to the problem of knowledge representation and prove the efficiency of combination of both discussed approaches.